Cartonist: Automatic Synthesis and Interactive Exploration of Nonstandard Carton Design. (September 2019) - Zhu, Lifeng; Xie, Benyi; Zhang, Yongjie Jessica; Yu, Lap-Fai
Abstract: Cartons are commonly used in the packaging industry, and standard carton patterns are broadly used in mass production. However, their designs may not fit different containees or specific fabrication requirements well. Taking the dimensions of the containees as input, we study the patterns of cartons and propose a system named "Cartonist" to efficiently explore the pattern variations. A synthesis algorithm is proposed to create a space of nonstandard carton patterns, based on which a design space exploration method is demonstrated. Cartonist enables a user to customize the design of carton patterns for different applications, considering design criteria such as material efficiency, folding ease and stability. We perform a user study to evaluate the effectiveness of our proposed system for carton design. Highlights: A system which helps design of nonstandard carton patterns. A procedural model for automatically synthesizing carton patterns. A method for exploring carton patterns with high-level requirements.